2017
DOI: 10.1017/s095927091600040x
|View full text |Cite
|
Sign up to set email alerts
|

Atlas data indicate forest dependent bird species declines in South Africa

Abstract: SummaryForest ecosystems in South Africa are at risk from a variety of anthropogenic threats impacting the faunal species dependent on them. These impacts often differ depending on species-specific characteristics. Range data on forest dependent bird species from the South African Bird Atlas Project (SABAP1 and SABAP2) were analysed to determine links between deforestation, species characteristics and range declines. Half of the species studied were found to have declining ranges. Range change data for these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…The responses of species to forest fragmentation are highly variable (Henle et al, 2004), and may result in no discernable effects (Berens et al, 2014), a loss of genetic diversity and increased population differentiation (Matolweni et al, 2000;McManus et al, 2015) or even extinction of forest specialists (Lawes, 2004;Olivier et al, 2013;Cooper et al, 2017;). The effects of fragmentation, although unlikely ever to be beneficial, are therefore unpredictable and remain poorly understood.…”
Section: Takedownmentioning
confidence: 99%
See 1 more Smart Citation
“…The responses of species to forest fragmentation are highly variable (Henle et al, 2004), and may result in no discernable effects (Berens et al, 2014), a loss of genetic diversity and increased population differentiation (Matolweni et al, 2000;McManus et al, 2015) or even extinction of forest specialists (Lawes, 2004;Olivier et al, 2013;Cooper et al, 2017;). The effects of fragmentation, although unlikely ever to be beneficial, are therefore unpredictable and remain poorly understood.…”
Section: Takedownmentioning
confidence: 99%
“…It nonetheless remains unclear whether wasp-assisted pollen flow can be sufficient to connect forest specialist fig trees into a single large genetic unit across sub-continental scales, especially given that the dispersal of Ficus seeds often extends for only short-distances, despite the services of strong flyers such as frugivorous birds (Zhou and Chen, 2010). Seed dispersal distances in South Africa may have been reduced further by the loss of forest specialist birds and mammals after their own populations responded to fragmentation (Lawes, 2004;Olivier et al, 2013;Cooper et al, 2017).…”
Section: Takedownmentioning
confidence: 99%
“…Habitat loss is one of the main extinction drivers in wild parrots globally (Collar 2000, Pain et al 2006. Despite the Cape Parrot experiencing a range decline of 59% in the past quarter century alone (Cooper et al 2017), recent census data suggests that the population is not in decline (Downs et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the impacts of invasive species can be seen as positive, even if the overall net impact is negative. For example, Cooper et al (2017) noted that the invasion of treeless landscapes by alien trees can provide nesting sites for native raptors and other birds, expanding their ranges; and Coleman and Hockey (2008) found that the invasion of bare rocky seashores by alien mussels has boosted populations of African Black Oystercatchers, Haematopus moquini). These types of effects can complicate management, and lead to conflict.…”
Section: How Do Biological Invasions Interact With Othermentioning
confidence: 99%